Healers on the colonial market; Native doctors and midwives in the Dutch East Indies - Hesselink, Liesbeth (Verhandelingen van het Koninklĳk Instituut voor Taal-, Land- en Volkenkunde, 2011)
Healers on the colonial market is one of the few studies on the Dutch East Indies from a postcolonial perspective. It provides an enthralling addition to research on both the history of the Dutch East Indies and the history of colonial medicine. This book will be of interest to historians, historians of science and medicine, and anthropologists. How successful were the two medical training programmes established in Jakarta by the colonial government in 1851? One was a medical school for Javanese boys, and the other a school for midwives for Javanese girls, and the graduates were supposed to replace native healers, the dukun. However, the indigenous population was not prepared to use the services of these doctors and midwives. Native doctors did in fact prove useful as vaccinators and assistant doctors, but the school for midwives was closed in 1875. Even though there were many horror stories of mistakes made during dukun-assisted deliveries, the school was not reopened, and instead a handful of girls received practical training from European physicians. Under the Ethical Policy there was more attention for the welfare of the indigenous population and the need for doctors increased. More native boys received medical training and went to work as general practitioners. Nevertheless, not everybody accepted these native doctors as the colleagues of European physicians. Liesbeth Hesselink (1943) received a PhD in the history of medicine from the University of Amsterdam in 2009. She has had a career in education and in politics. In addition she has published articles on prostitution and the medical history of the Dutch East Indies.